Students’ Perception on the Use of Self-Recording Video in English Class at Sintuwu Maroso University - Lamasigi, Eka Putri; Lantu, Ika Paramitha (Sintuwu Maroso Journal of English Teaching, 2023)
This study arranged that aims to describe students’ perceptions of the use of Self-Recording Video in English class at Sintuwu Maroso University. The data used for this study is directly collected through questionnaires given to students majoring in Public Administration, Management students and Law students. This research is based on a descriptive quantitative survey method. The research questionnaire uses a 4-point Likert scale with a range of 4 to 1. The results of this study indicate that students from the three majors have positive perceptions regarding to students’ perceptions of using Self-Recording Video on motivation to learn English, perceptions of using Self-Recording Video on student creativity and overall perceptions in implementing Self-Recording Video.